C-Reactive Protein As a Mediator of Complement Activation and Inflammatory Signaling in Age-Related Macular Degeneration - Chirco, Kathleen R.; Potempa, Lawrence A. (Frontiers in Immunology, 2018)
Age-related macular degeneration (AMD) is a devastating neurodegenerative disease affecting millions worldwide. Complement activation, inflammation, and the loss of choroidal endothelial cells (CECs) have been established as key factors in both normal aging and AMD; however, the exact mechanisms for these events have yet to be fully uncovered. Herein, we provide evidence that the prototypic acute phase reactant, C-reactive protein (CRP), contributes to AMD pathogenesis. We discuss serum CRP levels as a risk factor for disease, immunolocalization of distinct forms of CRP in the at-risk and diseased retina, and direct effects of CRP on ocular tissue. Furthermore, we discuss the complement system as it relates to AMD pathophysiology, provide a model for the role of CRP in this disease, and outline current therapies being developed and tested to treat AMD patients.